Comparison of Nutritional Content in Processed and Homemade Foods - Calais,Andrea; Thituson,Malin (2021)
This master thesis is performed in collaboration with Orkla Foods Sweden AB. The aim with this study is to investigate and compare nutritional contents in processed and homemade foods by investigating three selected ready meal products from the product range of Orkla Foods; meatballs, potato mash and pasta bolognese. This originates in a general perception that foods produced in a large-scale industry have a less adequate nutritional content compared to homemade foods. The experimental investigation was executed by having test subjects cooking homemade dishes by using industrial recipes and raw material provided by Orkla Foods, and by using corresponding home recipes and raw material from a grocery store. These two treatments and a control product, produced in a factory, were analyzed for a selection of nutrients, based on guidelines on what nutrients to encourage and limit in the diet. By combining these, a score called Nutrient Rich Food (NRF) index was created in order to have a suitable comparative measurement of the nutrient density in each dish. The results showed that in two out of three homemade dishes with home recipe, the meat-containing ones, the nutrient densities were significantly higher. This was mainly due to a higher meat content contributing to higher contents of protein and selected analyzed minerals. The addition of nutrient-dense vegetables, such as carrots, aided in increasing the dietary fiber and vitamin content in the pasta bolognese. In the third homemade dish, the potato mash, the nutrient density was not significantly different from the control. This was primarily because of the contents in the homemade dish which contained significantly more vitamin C which increases the nutrient density, but also significantly more saturated fat which decreases it. Furthermore, the homemade potato mash and its control seemed to be relatively similar despite the considerable difference in processing due to not that many significant differences were found. No significant differences were found in the energy content, the salt content, nor the portion sizes. The study also saw that the saturated fat content was depending on the fat content in the raw material, as well as the addition of butter and cheese. The result showed no difference in nutritional content when the processing of the food was performed industrially or at home, when using the same industrial recipe. The conclusion concerning the three selected ready meal products is that the largest impact of variation on the results and nutritional content in the processed and homemade variants originates from the differences in the home recipe and the industrial recipe. This is due to the addition of different raw materials in varying amounts, rather than the level of processing, i.e., the production scale and equipment used.
Keywords: food engineering; nutrition; processed food; homemade food; nutrient density; NRF index